Finland's nuclear waste solution. - Upson, S. (IEEE spectrum)
This article speaks about the nuclear waste solution in Finland. Posiva, the Finnish company building an underground repository here, says it knows how to imprison nuclear waste for 100 000 years. These multimillennial thinkers are confident that copper canisters of Scandinavian design, tucked into that bedrock, will isolate the waste in an underground cavern impervious to whatever the future brings: sinking permafrost, rising water, earthquakes, copper-eating microbes, or oblivious land developers in the year 25 000. If the Finnish government agrees-a decision is expected by 2012. This site will become the world's first deep, permanent repository for spent fuel.